Long-Term Effects of Adderall XR in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The long-term tolerability and effectiveness of extended release mixed amphetamine salts (Adderall XR) in children with attention deficit hyperactivity disorder (ADHD) were evaluated in a 24-month, multicenter, open-label extension of 2 placebo-controlled studies at UCLA, Massachusetts General Hospital, UC-Irvine, Maitland, FL, and Shire Pharmaceutical, Wayne, PA.